2004
DOI: 10.1111/j.0030-1299.2005.13537.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of genetic factors and population dynamics on the mating system of the hermaphroditic freshwater snail Biomphalaria pfeifferi

Abstract: P. 2005. The influence of genetic factors and population dynamics on the mating system of the hermaphroditic freshwater snail Biomphalaria pfeifferi . Á/ Oikos 108: 283 Á/296.Although self-fertilization and its evolutionary consequences have been widely studied, the relative influence of genetic and environmental factors on the determination of mixed-mating systems remains poorly known. In 1999 and 2000, we surveyed the mating system, the population dynamics and some life-history traits of four populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 78 publications
3
33
0
Order By: Relevance
“…Moreover, experimental conditions enforcing the presence of partners tend to decrease the selfing rate in selfing snail species, as shown in another highly selfing snail species, Bulinus truncatus, using molecular markers (P. David and P. Jarne, unpublished data). Low inbreeding depression is consistent with an average selfing rate of about 90 % in B. pfeifferi (Charbonnel et al, 2005). Genetic models of the evolution of the selfing rate indeed predict limited inbreeding depression (<0 .…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…Moreover, experimental conditions enforcing the presence of partners tend to decrease the selfing rate in selfing snail species, as shown in another highly selfing snail species, Bulinus truncatus, using molecular markers (P. David and P. Jarne, unpublished data). Low inbreeding depression is consistent with an average selfing rate of about 90 % in B. pfeifferi (Charbonnel et al, 2005). Genetic models of the evolution of the selfing rate indeed predict limited inbreeding depression (<0 .…”
mentioning
confidence: 57%
“…However, the observed mean selfing rate per population is about 90 % (Charbonnel et al, 2005), as observed in other species of freshwater snails (Viard et al, 1997 ;Trouve´et al, 2004). An open question is what maintains this residual outcrossing rate.…”
Section: (C) Limited Mating Activitymentioning
confidence: 85%
See 2 more Smart Citations
“…Populations may experience density variation associated with flooding and drought, leading to bottlenecks and recolonization events (Jarne and Delay, 1991;Charbonnel et al, 2002a,b). Analysis of the genetic structure of natural populations (Charbonnel et al, 2002a,b,c), progeny-arrays analyses (Charbonnel et al, 2005) and laboratory experiments (Tian-Bi et al, 2008) showed that B. pfeifferi is a highly selfing species. A consequence of both population demography and the mating system is limited neutral variability within populations and fairly large genetic differentiation among populations (Charbonnel et al, 2002a).…”
Section: Methodsmentioning
confidence: 99%